Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1. \(x^3-x+\frac{1}{2}=x^4-x^2+\frac{1}{4}+x^2-x+\frac{1}{4}=\left(x^2-\frac{1}{2}\right)^2+\left(x-\frac{1}{2}\right)^2\ge0\)
Nếu \(\left(x^2-\frac{1}{2}\right)^2+\left(x-\frac{1}{2}\right)^2=0\)thì \(\hept{\begin{cases}x-\frac{1}{2}=0\\x^2-\frac{1}{2}=0\end{cases}=>\hept{\begin{cases}x=\frac{1}{2}\\x^2=\frac{1}{2}\end{cases}}}\)(VÔ LÍ)
Vậy \(x^4-x+\frac{1}{2}>0\)
\(A=\dfrac{4a+2b-6b-8a+4b}{\left(2a-b\right)\left(2a+b\right)}:\dfrac{4a^2-b^2+4a^2+b^2}{\left(2a-b\right)\left(2a+b\right)}\)
\(=\dfrac{-4a}{\left(2a-b\right)\left(2a+b\right)}\cdot\dfrac{\left(2a-b\right)\left(2a+b\right)}{8a^2}=\dfrac{-1}{2a}\)
xét hiệu
\(\left(a+2\right)^2-8a\ge0\)
<=> \(a^2+4a+4-8a\ge0\)
<=> \(a^2-4a+4\ge0\)
<=>\(\left(a-2\right)^2\ge0\) (luôn đúng)
=> đpcm
a) \(a^4-5a^2+4=\)\(\left(a^4-4a^2\right)-\left(a^2-4\right)=a^2\left(a^2-4\right)-\left(a^2-4\right)=\left(a^2-1\right)\left(a^2-4\right)\)
\(=\left(a-1\right)\left(a+1\right)\left(a-2\right)\left(a+2\right)\)
\(a^4-a^2+4a-4=a^2\left(a^2-1\right)+4\left(a-1\right)=a^2\left(a-1\right)\left(a+1\right)+4\left(a-1\right)\)
\(=\left(a-1\right)\left[a^2\left(a+1\right)+4\right]=\left(a-1\right)\left(a^3+a^2+4\right)\)
\(a^3+a^2+4=\left(a^3+2a^2\right)-\left(a^2+2a\right)+\left(2a+4\right)=a^2\left(a+2\right)-a\left(a+2\right)+2\left(a+2\right)\)
\(=\left(a^2-a+2\right)\left(a+2\right)\)
\(N=\frac{\left(a-1\right)\left(a+1\right)\left(a-2\right)\left(a+2\right)}{\left(a-1\right)\left(a+2\right)\left(a^2-a+2\right)}=\frac{\left(a+1\right)\left(a-2\right)}{a^2-a+2}\)
\(=\left(\dfrac{2}{2a-b}-\dfrac{6b}{\left(2a-b\right)\left(2a+b\right)}-\dfrac{4}{2a+b}\right):\dfrac{4a^2-b^2+4a^2+b^2}{4a^2-b^2}\)
\(=\dfrac{4a+2b-6b-8a+4b}{\left(2a-b\right)\left(2a+b\right)}\cdot\dfrac{\left(2a-b\right)\left(2a+b\right)}{8a^2}\)
\(=\dfrac{-4a}{8a^2}=\dfrac{-1}{2a}\)
\(=\left(\dfrac{2\left(2a+b\right)-6b-4\left(2a-b\right)}{\left(2a-b\right)\left(2a+b\right)}\right):\dfrac{4a^2-b^2+4a^2+b^2}{\left(2a-b\right)\left(2a+b\right)}\)
\(=\dfrac{4a+2b-6b-8a+4b}{8a^2}\)
\(=\dfrac{-4a}{8a^2}=\dfrac{-1}{2a}\)
\(4a^4+5a^2\ge8a^3+2a-1\)
\(\Leftrightarrow4a^4+5a^2-8a^3-2a+1\ge0\)
\(\Leftrightarrow\left(4a^4-8a^3+4a^2\right)+\left(a^2-2a+1\right)\ge0\)
\(\Leftrightarrow\left(2a^2-2a\right)^2+\left(a-1\right)^2\ge0\)
\("="\Leftrightarrow a=1\)
Cảm ơn bạn rất nhiều